IC 8012 Mining, Milling, And Water-Control Methods, Rosiclare Fluorspar Works, Aluminum Co. Of America ? Introduction And Summary - Ronald W. Schaefer (The National Institute for Occupational Safety and Health (NIOSH), 1961)
This report describes operations at the Rosiclare Fluorspar Works of the Aluminum Co. of America at Rosiclare, Hardin County, Ill. The works include the Fairview mine, the fluorspar mill, and related facilities. The publication covers exploration, development, mining and milling practices, mine-drainage problems, and other activities and is presented as part of the Bureau of Mines series of publications on mining and milling practices in various parts of the United States. The Rosiclare fluorspar area, for its size, has been the largest producer of high-grade fluorspar in the United States and probably in the world. The vein system in this area is over 5 miles long and 1/2 mile wide, and ore has been found as deep as 900 ft.